Using Formal Specification to Validate a Human Resource Information System - Maskuri, Rohidah; Mohd. Zin, Abdullah (Malaysian Journal of Computer Science, 1999)
This paper contains the analysis of the Z specification of a human resource information system. It aims to show the strength of the formal methods in analysing and detecting errors after the implementation phase.